Modulation of NF-κB Signaling as a Therapeutic Target in Autoimmunity. (March 2016) - Herrington, Felicity D.; Carmody, Ruaidhrí J.; Goodyear, Carl S.
Autoimmune diseases arise from the loss of tolerance to endogenous self-antigens, resulting in a heterogeneous range of chronic conditions that cause considerable morbidity and mortality worldwide. In Western countries, over 5% of the population is affected by some form of autoimmune disease, with enhanced or inappropriate activation of nuclear factor (NF)–κB implicated in a number of these conditions. Although treatment strategies for autoimmunity have improved significantly in recent years, current therapeutics are still not capable of achieving satisfactory disease management in all patients, and as such, the therapeutic modulation of NF-κB is an attractive target in autoimmunity. To date, no NF-κB inhibitors have progressed to the clinic for the treatment of autoimmunity, but a variety of promising approaches targeting multiple stages of the NF-κB pathway are currently being explored. This review focuses on the current strategies being investigated for the inhibition of the NF-κB pathway in autoimmune diseases and considers potential future strategies for the therapeutic targeting of this crucial transcription factor.